Transit-Oriented Development Indicators for Suburban Railway Stations in Thailand: A Context-Specific Fuzzy Delphi Approach - Sangsrichan, Chaiwat; Sungtrisearn, Patcharida; Pichayapan, Preda (Journal on Transportation System and Engineering, 2025)
This study identifies suitable indicators for Transit-Oriented Development (TOD) in suburban areas of Thailand using the Fuzzy Delphi Method to gather expert consensus. While TOD has been extensively studied in urban cores, suburban regions with distinct characteristics, including lower densities, tropical climates, and prevalent informal transportation, have received limited attention. The research examined 48 indicators from international literature across three components: Transit System Indicators, Oriented System Indicators, and Development System Indicators. Through two rounds of expert consultation with ten professionals, 44 indicators were accepted, while four were rejected as being contextually inappropriate. Train service frequency (0.950), pedestrian walkway width (0.940), and mixed land use (0.940) emerged as the highest priorities. Rejected indicators included station retail outlets (0.710), pedestrian pathway gradient (0.670), high-rise building areas (0.670), and government service centers (0.677), revealing fundamental differences between suburban and urban TOD contexts. Three key themes emerged: climate-responsive infrastructure is essential in tropical environments, informal transportation modes require integration rather than elimination, and suburban development should pursue moderate-density horizontal mixed-use patterns rather than high-density urban forms. These findings provide practical guidance for evaluating and planning TOD around Thailand’s expanding suburban railway network, supporting effective resource allocation and implementation strategies aligned with suburban realities while advancing sustainable mobility objectives.